ROLE OF PUBLIC SECTOR UNIVERSITIES IN PROMOTING HIGHER EDUCATION THROUGH DISTANCE EDUCATION IN PAKISTAN - Ms. Nadia (International Islamic University Islamabad, 2018)
Present research focused to know the role of public sector universities in promoting higher education through distance education in Punjab, Pakistan was conducted to evaluate the support services like reading material, teaching faculty, study Centre support, assignments, assessment, correspondence, use of instructional technology and teaching strategies. An additional concern of the study was to explore the problems and facilities in public sector universities for their distance learners. Population of this study was consisted 92 teachers of three public sector universities (GCUF, BZU & IUB) of distance education programs. The study was descriptive by nature therefore questionnaire for teachers was used for data collection. Data were collected, screened, tabulated, analyzed, and interpreted through using SPSS v21.0. Data was interpreted through applied statistics using mean, standard deviation, chi-square and t-value. Results revealed that reading material, assignments, assessment, correspondence and instructional technology systems was partly fulfilling the requirements whereas study centers support, assignments and access services were needed to be updated.